Seismic Analysis of RCC Building With And Without Floating Column Using STAAD Pro V8i - Shail Agrawal (AG Volumes, 2021)
Ground vibrations may cause moderate to severe damage to many reinforced concrete structures in metropolitan areas that are located in active seismic zones. Architectural design and the frame drawing of a structure with floating columns are the focus of this project. The consequences of the load distribution on the floating columns are also being examined. The path of action of force is also examined for its significance and impacts. We’re comparing the seismic analysis of multistory buildings with and without floating columns in this research. STAAD Pro V8i is being used to do an analogous static analysis on the whole mathematical 3D model of the project and the resulting models are being compared. Floating columns are used in many structures, particularly those above ground level, to provide additional open space for parking and other purposes.